Multifunctional Self‐Charging Electrochromic Supercapacitors Driven by Direct‐Current Triboelectric Nanogenerators. (23rd June 2021) - Guo, Wenbin; Cong, Zifeng; Guo, Zi Hao; Zhang, Panpan; Chen, Yanghui; Hu, Weiguo; Wang, Zhong Lin; Pu, Xiong
Abstract: Electrochromic supercapacitor devices (ESCDs) are highly promising for energy‐saving applications or smart windows, whereas they still require electrical energy inputs. In this study, a self‐charging ESCD (SC‐ESCD) based on the ESCD and a sliding‐mode direct‐current triboelectric nanogenerators is successfully proposed. The SC‐ESCD cannot merely convert mechanical sliding kinetic energy into electrical energy and store the electricity in electrochromic supercapacitors but can also show optical responses to the mechanical sliding motions. The prominent electrochemical performances of the SC‐ESCD are confirmed by the high areal capacitance (15.2 mF cm −2 at 0.1 mA cm −2 ) and stable cycling performance (99% for 5000 cycles). Besides, it can be prepared into arbitrary characters or patterns to adapt to various applications. The study demonstrates a potential approach to develop multifunctional self‐charging power sources which combine energy harvesting, energy storage, and electrochromic functions. Abstract : Self‐charging electrochromic supercapacitor devices are demonstrated, which cannot only scavenge and store the sliding kinetic energy but also show optical responses according to the mechanical motions.